Metode TaḤfīẒ Al-Qur'ān Di Sdip Al-Madinah PutraTahun Pelajaran 2016/ 2017 - Nugraha, Muhammad Iqbal Pria; , Drs. M. Darojat Ariyanto, M.Ag (2017)
Male Al-Madinah Islamic Elementary School (SDIT) Makamhaji is one of Elementary School which is under shelter of Al-Madinah Foundation. The purpose of establishing this school was to facilitate and to give option to the parents who want to educate their children in the Elementary School. The type of this school is Islamic Elementary School (SDIT). This school has many advantages than another school that is attaining of memorizing Al-qur'ān of the students. Usually the students only can memorize Al-qur'ān 1 until 2 Juz, but in this school they can memorize it 5 until more than it. So that, the researcher wanted to observe, why this school is different with other schools. The aim of this research was to know the method which is used by the teacher to request the students to memorize Al-qur'ān . Type of this research was field research, but using qualitative descriptive approach. The method of collecting the data used interview, documentation, and observation. Meanwhile, the method of analyzing data used was qualitative descriptive with inductive analysis. Based on the observation, it could be concluded that the method of taḥfīẓ Al-qur'ān which is used at Islamic Elementary School (SDIT) is talqin. This method is while doing teaching and learning in the class, the teacher must organize the class and then he/she reads the holy Al-qur'ān which wants to be memorized, after that the students follow their teacher, this way repeated in many time. All of degrees in that school use it from I until VI grades. By using talqin method, it could be concluded that the process of teaching learning by utilizing taḥfīẓ Al Quran at Al-Maidah Islamic Elementary School (SDIT) was effective. It was proved from the attaining all of sixth grade students who can memorize 5 Juz. These things is suitable with what are the instructors ever wanted. Although every student has their own variation mark in memorizing, but their mark are already fulfilled standard mark of taḥfīẓ (KKM) that have been decided by school officers.